Ontological issues in evolutionary economics: The debate between Generalized Darwinism and the Continuity Hypothesis - Jack Vromen (Max Planck Institute of Economics, 2008)
Hodgson and Knudsen's Generalized Darwinism (GD) and the Continuity Hypothesis (CH) put forward by Witt are currently vying for hegemony in the ontology of evolutionary economics. GD and the CH allegedly advance rivaling Darwinian foundations for the development of full-fledged causal evolutionary economic theories. Yet upon closer inspection it is not clear that GD and the CH are mutually exclusive rivals. For one thing, GD and the CH address different sorts of issues. Whereas GD aims at identifying general features that evolutionary processes in different domains (notably the biological and economic domain) have in common, the CH takes as its starting point the causal relations that obtain between antecedent biological evolution and ongoing economic evolution. It seems the one does not exclude the other. This impression is strengthened by the fact that Hodgson endorses rather than opposes something similar to the CH. The paper argues that the critical issue in settling whether or not GD and the CH are mutually exclusive is how much substantive content is given to GD and the CH respectively. Pushed by the critique of Witt (and some of his Evolutionary Economics Group members, Cordes and Buenstorf) that GD has not fully shaken off features that are specific for the biological domain, Hodgson and Knudsen seem to take recourse to a version of GD that is so abstract and general that it is rendered virtually vacuous. As such GD can not contribute much to the development of a full-fledged domain-specific causal economic theory of processes of economic change. It seems the CH fares better in this respect. The CH does offer building blocks for evolutionary theories of consumption and of production. But the problem with the GD is that it is unclear what constructive role (if any) Darwinian evolutionary theory has played in specifying the building blocks. The paper concludes with suggesting two other ways in which Darwinian evolutionary theory might be useful for studying economic evolution.
Keywords: 330; Evolutionsökonomik; Ontologie; Dogmengeschichte